2018
DOI: 10.3389/fpsyg.2018.00592
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Dissonance, Mental Health Complaints, and Sickness Absence Among Health- and Social Workers. The Moderating Role of Self-Efficacy

Abstract: Health- and social workers are frequently exposed to emotionally demanding work situations that require emotion regulation. Studies have demonstrated a direct relationship between emotion regulation and health complaints and sickness absence. In order to prevent health complaints and to reduce sickness absence among health- and social workers, there is need for greater attention to mechanisms explaining when and how emotionally demanding work situations are related to employee health and sickness absence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 54 publications
(68 reference statements)
1
31
1
4
Order By: Relevance
“…The second objective of this study sought to determine whether SE, in addition to this mediating role, also moderates the relationship between EWB and the use of ACS. Although diverse studies carried out in work settings highlight the important moderating role played by SE in preventing stress in conditions of low personal psychological adjustment [45,46]; our data does not confirm this assumption. Thus, contrary to what was hypothesized, we did not find a significant interaction between EWB and SE with regard to its effect on ACS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The second objective of this study sought to determine whether SE, in addition to this mediating role, also moderates the relationship between EWB and the use of ACS. Although diverse studies carried out in work settings highlight the important moderating role played by SE in preventing stress in conditions of low personal psychological adjustment [45,46]; our data does not confirm this assumption. Thus, contrary to what was hypothesized, we did not find a significant interaction between EWB and SE with regard to its effect on ACS.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research offers only indirect evidence regarding this issue. It has been observed in work environments that individuals who experience symptoms of poor psychological adjustment (in the form of role overload and conflict, emotional dissonance, low perceived autonomy, or low satisfaction) with high levels of self-efficacy tend to evaluate demands as challenges [28] and engage in functional coping strategies [45], which leads them to experience low levels of stress [46].…”
Section: Introductionmentioning
confidence: 99%
“…Indregard et al 39 reported that health care providers and social workers who frequently experience emotional dissonance had higher levels of exhaustion and mental distress, indicating that health care workers are at high risk of mental health disorders or illness. Furthermore, some effects on emotional health were reported, such as superficial emotional control, emotional expression, emotional expressionincited emotion disorder, and interaction extent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some effects on emotional health were reported, such as superficial emotional control, emotional expression, emotional expressionincited emotion disorder, and interaction extent. 39 These should be addressed within the workplace to prevent the development of issues related to mental health issues. 8,40 Delgado et al 41 stressed that the ability to deal with the conflict of work rights and duty is required for workers who interact with patients and their family members in hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation